CONTRACTIONWAVE: Software baseado em fluxo óptico denso para quantificar a contratilidade celular - Sérgio Ricardo Aluotto Scalzo Júnior (2021)
Quantification of cardiomyocyte contractility is an essential biomedical task and a key step in understanding the mechanisms involved in the pathogenesis of cardiac disease. However, accurate and reproducible measurements are hampered by several factors inherent to the software options currently available. Therefore, our goal was to develop an innovative technology to quantify the biomechanics of cardiomyocytes through robust open-source software written in Python language. We used cell images obtained from bright field microscope, and processed by dense optical method. To validate the software efficiency, we exposed male adult (12 weeks), neonatal (1-3 days) and Human-induced pluripotent stem cell-derived cardiomyocytes (hiPSCM) to drugs known to affect contractility (Isoproterenol or Verapamil). Statistical analysis was performed using ANOVA and Test t student, using p<0.05. Thus, we developed CONTRACTIONWAVE (CW), an open-source software written in Python language that combines in a single platform a robust method to acquire, visualize, analyze, and quantify contractility parameters of cardiac cells at different developmental stages. CW presents innovative features: 1) the Dense optical flow algorithm makes the program more sensitive; 2) CW can automatically detect contraction-relaxation average speed parameters and frequency; 3) CW interface was designed for users that are not a specialist in the cardiovascular field, therefore achieving a wide audience; 4) CW provides a novel visualization feature that permits simultaneous viewing of the cell image and the contraction waves. Adult, Neonatal and hiPSCM cardiomyocytes, treated with ISO or VERA, showed a significant decrease in Contraction Time, Relaxation and Total Contraction-Relaxation (ms). Only cells treated with VERA showed a decrease in the Maximum Contraction Speed (µm/s) and Maximum Relaxation Speed (µm/s) while the ISO increased. Likewise, ISO and VERA induced opposite effects in the shortening area (µm²). Cardiomyocytes from a hypertension model showed an increase in contraction time. Taken together, our results shows that CONTRACTIONWAVE is a high power open-source software to analyze cardiac contraction parameters, streamlining drug testing, disease modeling and advancing basic research in the cardiac.